Exploring the diverse phenotypes of anti-GAD 65 encephalitis, diagnosis and treatment challenges - Octaviana Adriana Dulamea; Anca Adriana Arbune; Andreea Andronache; Lorenzo Giovanni Zurini; Daniela Anghel (Romanian Journal of Neurology)
Objectives. To present two cases of anti-glutamic acid decarboxylase 65 (anti-GAD65) antibody encephalitis with different clinical phenotypes. Introduction. Anti-glutamic acid decarboxylase 65 antibody encephalitis (GAD-65 AE) is a rare pathology with a high potential for severity, having multiple forms of presentation and multiple differential diagnoses. This presentation aims to exemplify the strong clinical heterogeneity that is associated with this clinical entity by putting forth two cases that were treated in our clinic, each representing a separate clinical phenotype of this pathology. Material and methods. We analyzed two cases from our clinic of autoimmune encephalitis with positive anti-GAD65 antibodies and compared the cases with the data from the literature regarding clinical presentation, differential diagnosis, treatment, and evolution. Content. The first case presented is a woman aged 71 (66 at onset) presenting with progressive cerebellar ataxia. She was diagnosed with GAD-65 AE based on clinical presentation and positive anti-GAD65 antibodies titer. She was initially treated with methylprednisolone pulse therapy and received four such courses in the first year after diagnosis, resulting in a slowing of the progression of the neurological deficit. During the COVID19 pandemic, treatment was paused and her neurological status resumed its decline, and she also developed insulin-dependent diabetes mellitus. Starting in 2021, treatment was continued, having received one course of IVIg and one course of plasma exchange in our clinic. Eventually, the treatment was switched to Mycophenolate mofetil but her status continues to decline. The second case is about a 32 years old woman, with a history of recurrent seizures and progressive memory decline that started at 28 years. She was diagnosed 11 months after the onset with limbic encephalitis with anti-GAD65 antibodies, left temporal focal epilepsy with nocturnal seizures and mild cognitive decline. She was treated with corticotherapy and IgG. She was discharged home with antiepileptic treatment with no recurring seizures, but a slow cognitive decline. She had two relapses at distance from the onset, the first one with status epilepticus and the second one with focal seizures and a generalized seizure. She developed type I diabetes with positive anti-pancreatic islet antibodies. After the first relapse, immunosuppressive therapy with Mycophenolate mofetil was initiated. The evolution was good and under immunosuppression she had only one episode of seizures in the context of a COVID-19 infection. Conclusions. Autoimmune encephalitis with positive GAD antibodies presents a very diverse clinical picture, as we can see in the presented cases.